(untitled) (Journal of the College of Basic Education, 2022)
The current study aimed to examine the effectiveness of play therapy in reducing the symptoms of post – traumatic stress disorder among a sample of sexually abused children. The sample consisted of (30) sexually abused children in Al Hussein Foundation for Social Services in Jordan . The study sample was divided into a control group, which consisted of (15) children (8 males and 7 females), and an experimental group which consisted of (15) children (8 males and 7 females). The ages of the study sample ranged from (6) to (12) years old for both groups. The individuals of the experimental group were subject to a play – based psychotherapy program, while the control group did nit receive any therapeutic intervention. The program consisted of (30) play – based psychotherapy sessions, and (20) individual therapy sessions. The program contained the following therapeutic techniques.Expression through art, play with puppets, storytelling, and play group therapy .The result of study showed statistically significant differences. Between control and experimental groups at level (0.05), therefore the effectivemess of the therapy program used in reducing the symptoms of P.T.S.D the researcher discussed the results and write the recommendation.